Synthesis and electrical characterization of cold sintered Ba0.7Sr0.3TiO3–PVDF ceramic nanocomposites for capacitive energy storage applications - Dwivedi A.; Singh V.P.; Dwivedi A.; Singh A.K. (My University, 2025)
The lead-free dielectric capacitors with high-temperature stability, high energy storage density and high discharge efficiency are highly needed for pulse power and power electronic applications. In this regard, Ba0.7Sr0.3TiO3–PVDF (Polyvinylidene fluoride) ceramic-polymer composites have been synthesized using a cold sintering process. Ba0.7Sr0.3TiO3 (BST) nanopowder was synthesized using sol–gel combustion method. The BST nanopowder was used for synthesizing the Ba0.7Sr0.3TiO3–PVDF composite with 80 wt% BST and 20 wt% PVDF. X-ray diffraction analysis confirmed pure phase formation of BST and revealed presence of different phases of PVDF in certain conditions. Thermal stability and surface morphology of the composite has been studied using thermo-gravimetric analysis and SEM, respectively. Dielectric and ferroelectric properties have been studied. Polarization-Electric field hysteresis loop analysis of composite reveals that significantly higher dielectric breakdown strength (more than 400 kV/cm) have been achieved in comparison to pure ceramic which is the main criteria for a potential material for energy storage purpose. Discharge efficiency of BST/PVDF annealed composite upto 95% and high thermal stability up to 300 °C has been achieved in the present case. © 2023, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.